Hox-Positive Adult Mesenchymal Stromal Cells: Beyond Positional Identity - Kulebyakina, Maria; Makarevich, Pavel (Frontiers in Cell and Developmental Biology, 2020)
Homeobox proteins (Hox) are universal regulators of body patterning process in embryogenesis of metazoan. The Hox gene expression pattern (Hox code) retains in adult tissues and serves as cellular positional identity marker. Despite previously existing notions that the Hox code is inherent in all stroma mesenchymal cells as a whole, recent studies have shown that the Hox code may be an attribute of a distinct subpopulation of adult resident mesenchymal stromal cells (MSC). Recent evidence allows to suggest a “non-canonical” role for Hox genes expression which is associated with renewal and regeneration in postnatal organs after damage. In tissues with high regenerative capacity it has been shown that a special cell population is critical for these processes, a distinctive feature of which is persistent expression of tissue-specific Hox genes. We believe that in the postnatal period Hox-positive subpopulation of resident MSC may function as a unique regenerative reserve. These cells coordinate creation and maintenance of correct structure of the stroma through a tissue-specific combination of mechanisms. In this article, we summarize the data on the role of resident mesenchymal stromal cells that have a tissue-specific pattern of Hox gene expression as regulators of processes necessary for correct reconstruction of the tissue.